2020
DOI: 10.1002/chem.202001261
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Molecular Basis of Avibactam‐Mediated Inhibition of Class A β‐Lactamases

Abstract: Disseminating antibiotic resistance rendered by bacteria against the widely used β−lactam antibiotics is a serious concern in the public health care. Development of inhibitors for drug-resistant β−lactamase enzymes is vital to combat this rapidly escalating problem. Recently, the Food and Drug Administration has approved a non-βlactam inhibitor called avibactam for the treatment of complicated intra-abdominal and urinary tract infections caused by drug-resistant Gram-negative bacteria. This work sheds light on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…They inhibit the bacterial-cell-wall-synthesizing enzymes known as penicillin binding proteins (PBPs). , However, the clinical efficacy of these life-saving drugs progressively deteriorates due to the emergence of drug resistance in bacteria, primarily associated with the expression of β-lactamases. These enzymes hydrolyze β-lactam antibiotics in an efficient manner, preventing the drug molecules to react with PBPs. In the past, our group contributed to the understanding of the mechanism of hydrolysis of different classes of β-lactamases. , Here, we focus on class C serine β-lactamases that are majorly responsible for hospital-acquired infections. It was found that the protonation states of the active-site residues Lys 67 and Tyr 150 of class C β-lactamase play a crucial role in determining the hydrolysis mechanism. ,, In the Michaelis complex of cephalothin and the enzyme, two protonation states are to be considered: K + Y – and KY .…”
Section: Results and Discussionmentioning
confidence: 99%
“…They inhibit the bacterial-cell-wall-synthesizing enzymes known as penicillin binding proteins (PBPs). , However, the clinical efficacy of these life-saving drugs progressively deteriorates due to the emergence of drug resistance in bacteria, primarily associated with the expression of β-lactamases. These enzymes hydrolyze β-lactam antibiotics in an efficient manner, preventing the drug molecules to react with PBPs. In the past, our group contributed to the understanding of the mechanism of hydrolysis of different classes of β-lactamases. , Here, we focus on class C serine β-lactamases that are majorly responsible for hospital-acquired infections. It was found that the protonation states of the active-site residues Lys 67 and Tyr 150 of class C β-lactamase play a crucial role in determining the hydrolysis mechanism. ,, In the Michaelis complex of cephalothin and the enzyme, two protonation states are to be considered: K + Y – and KY .…”
Section: Results and Discussionmentioning
confidence: 99%
“…This method is suited to study systems with broad, flat, and unbound free energy landscapes. This method has been applied to study various problems 59–64 and has also been extended to deal with high‐dimensional CV‐space 47 . By combining REST2 with WSMTD, we hope to boost the sampling of hidden transverse coordinates while exploring the relevant CV space.…”
Section: Introductionmentioning
confidence: 99%
“…This warrants a thorough mechanistic investigation. A detailed molecular-level investigation deciphering the inhibition mechanism of avibactam by class A and C SBLs was reported by us earlier. , …”
Section: Introductionmentioning
confidence: 89%
“…It uses an umbrella sampling bias for a controlled sampling of a CV along which a broad and unbound basin is expected, whereas the orthogonal coordinates are sampled using a well-tempered metadynamics bias and high temperature. , In conventional metadynamics, the negative sum of the total augmented bias potentials gives a good estimation of the underlying free energy, while for TASS, the same is obtained from a reweighted distribution of CVs, as described in ref . It is worth mentioning that TASS and metadynamics were successfully used in many of our previous studies for modeling chemical reactions. ,, …”
Section: Methodsmentioning
confidence: 99%